Secular trends in childhood pain and comorbid psychiatric symptoms: a population-based study - Luntamo Terhi; Lempinen Lotta; Sourander Andre (Springer, 2022)
Purpose Pain symptoms are common in childhood. They often lead to functional impairment and co-occur with psychiatric difficulties. Although children's lives have undergone enormous changes in recent decades, long-term data on changes in pain symptoms, and in comorbid psychiatric difficulties, is lacking. This knowledge is crucial, as co-occurring psychiatric symptoms are significant predictors of long-term outcome for children who suffer from pain. The main purpose of the present study was to explore secular changes in comorbid pain and psychiatric symptoms. Methods Four population-based, cross-sectional surveys of 8-9-year-old children were conducted in Southwest Finland in 1989, 1999, 2005, and 2013. Identical methodologies and questionnaire-based measures were used each study year. Participation ranged from 891 to 986 over the study period. The children were asked about the frequency of headache, abdominal pain, and other pains. Children, their parents, and teachers provided information on the child's psychiatric difficulties, including internalizing and externalizing symptoms. Results The cumulative odds ratios and 95% confidence intervals for the overall prevalence of pain symptoms increased among both genders from 1989 to 2013 and ranged from 1.4 (1.03-1.8) for other pains to 2.4 (1.7-3.3) for abdominal pain. Comorbid internalizing symptoms increased among girls with odd ratios and 95% CIs of 1.8 (1.03-3.1) for children with any kind of pain, and 3.0 (1.4-6.2) for children with headache. No changes were found among boys. Conclusion Overall pain symptoms doubled in both genders, but the most novel finding was that comorbid emotional difficulties tripled among girls who reported headaches. Further research is needed to confirm, and explain, these findings.